Complexity, Uncertainty and Ambiguity in Korean Military Leadership - OH, LEE JONG (Advances in Social Sciences Research Journal, 2022)
In South Korea, being the only divided country in the world and thus being under extreme tension, the weight and the importance that the Korean military carries is surely different from those of other militaries. Under this exceptional circumstance, it is not an overstatement to say that the Korean military faces a more complex and difficult challenge than any other organization and requires a higher state of leadership. The sinking of the Cheonan navy vessel and the bombardment of Yeonpyeong Island on the west coast of South Korea in 2010 were opportunities to look back upon the present state of the leadership of the Korean military. Internally, the Korean military is making efforts to justify its existence, and within the military, it is trying to develop its organizational leadership that can contribute to meeting its objectives. The discussion across society centered on national defense reforms supports this notion, which tells us that reflecting on the organizational leadership to perform the roles of the military is the central task in order to shift the organizational paradigm that meets the changes of security environments surrounding south Korea and far eastern Asia. Under these circumstances, it is imperative and timely to discuss a few phenomena that hinder the development of the military leadership and to look for alternatives.